Improving Financial Management Behavior Through Financial Attitude, Financial Knowledge, And Financial Technology in Students STIE Graha Kirana Medan - nur subiantoro (Enrichment : Journal of Management, 2022)
This study aims to determine and analyze the influence of Financial Attitude, Financial Knowledge and Financial Technology on the Financial Management Behavior of STIE Graha Kirana students. The population in this study is STIE Graha Kirana Stambuk 2016-2018 students who use an unknown number of fintech. The number of samples in this study was 96 students with an accidental sampling technique. Data collection methods are questionnaires and interviews. The analysis technique uses multiple linear regression analysis. The results of this study indicate that simultaneously financial attitude, financial knowledge, and financial technology have a significant and significant effect on financial management behavior. Partially, the Financial Attitude and financial knowledge variables have a positive and significant effect on Financial Management Behavior, while the Financial Technology variable has a positive and insignificant effect on Financial Management Behavior